1999
DOI: 10.1002/(sici)1096-9896(199912)189:4<521::aid-path472>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Different genetic pathways in the evolution of invasive breast cancer are associated with distinct morphological subtypes

Abstract: Invasive breast cancer shows a wide range of morphological differentiation, associated with differences in prognosis, but as yet, the underlying genetic mechanisms cannot be accounted for. In order to establish a model of the possible progression from the different subtypes of ductal carcinoma in situ (DCIS) to invasive breast cancer, 77 selected cases of invasive breast cancer representing distinct morphological subtypes were investigated by means of comparative genomic hybridization (CGH). There was a high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
169
1
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(187 citation statements)
references
References 15 publications
15
169
1
2
Order By: Relevance
“…This is expected, given that only breast carcinomas of histological grades 2 and 3 were present in the population and gains of 8q are rather frequent in grade 2 and 3 breast cancers (Buerger et al, 1999a, b;Roylance et al, 1999). The comparison between the genomic profiles obtained for ductal and lobular carcinomas were also in agreement with previous studies (Buerger et al, 1999b;Shelley Hwang et al, 2004;Reis-Filho et al, 2005a;Simpson et al, 2005;Stange et al, 2006): gain of 1q and deletions of 16q were the most prevalent changes in lobular carcinomas, whereas gain of 8q was significantly more frequent in grade 2 and 3 ductal carcinomas. However, we could define the smallest region of overlap of the deletions of 16q, which mapped to 16q21 -q22.1 and encompassed the region of the cadherin gene cluster, and the gain of 8q, which encompassed two regions 8q13.2 -q21.13 and 8q21.3 -qtel (Supplementary Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…This is expected, given that only breast carcinomas of histological grades 2 and 3 were present in the population and gains of 8q are rather frequent in grade 2 and 3 breast cancers (Buerger et al, 1999a, b;Roylance et al, 1999). The comparison between the genomic profiles obtained for ductal and lobular carcinomas were also in agreement with previous studies (Buerger et al, 1999b;Shelley Hwang et al, 2004;Reis-Filho et al, 2005a;Simpson et al, 2005;Stange et al, 2006): gain of 1q and deletions of 16q were the most prevalent changes in lobular carcinomas, whereas gain of 8q was significantly more frequent in grade 2 and 3 ductal carcinomas. However, we could define the smallest region of overlap of the deletions of 16q, which mapped to 16q21 -q22.1 and encompassed the region of the cadherin gene cluster, and the gain of 8q, which encompassed two regions 8q13.2 -q21.13 and 8q21.3 -qtel (Supplementary Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…Loss of 8p was also observed at significantly lower fre- quency in other types of breast cancers, 16,17,19,22 therefore, it can be considered as a potential locus harbouring a breast cancer susceptibility gene. There are a number of candidate genes within the region lost on the short arm of chromosome 8.…”
Section: Discussionmentioning
confidence: 97%
“…For example, the results obtained on sporadic cases in our study, non-familial tumours reported by others, as well as BRCA2-associated breast cancers showed a correlation between 8p-losses and positive lymph node status as well as higher tumour grading. 17,19,24,25 This evidence suggests that tumour suppressor genes located in 8p are more likely to be associated with tumour progression rather than initiation in this type of breast cancer. In our set of BRCAX tumours the frequencies of chromosome 8p loss was similar in Grade II and Grade III tumours, but was observed more frequently in tumours with negative (6/9 vs. 4/9) lymph node status.…”
Section: Discussionmentioning
confidence: 98%
“…In several studies, chromosome 1q and 16q imbalances have been investigated separately: chromosome 1q gains have been found at any stage, [18][19][20] whereas chromosome 16q losses have been mostly detected in low and intermediately differentiated carcinoma 3,4 or in invasive lobular carcinoma. 21 Altogether, these data supported the hypothesis that low/intermediate-and high-grade breast carcinoma develop according to distinct pathways: chromosome 16q loss was proposed as a marker of a distinct genetic pathway in breast carcinoma development.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Gains of the long arm of chromosome 1 and losses of chromosome 16q are often the result of unbalanced translocations between these two chromosomes: 1,6 less frequently, they are the result of other rearrangements. 2,5 Chromosome 1q gains and 16q losses are considered as early changes since they have been detected as the sole chromosome abnormalities in near-diploid breast carcinoma 1,6 and in well-differentiated samples with a few alterations.…”
mentioning
confidence: 99%